Characterization and identification of potential cellulolytic bacteria for bio-degradation of durian shell waste in Mekong Delta, Vietnam - TRUONG QUOC TAT; NGUYEN DUY KHANH; QUACH VAN CAO THI (Society for Indonesian Biodiversity, 2024)
Abstract. Tat TQ, Khanh ND, Thi QVC. 2024. Characterization and identification of potential cellulolytic bacteria for bio-degradation of durian shell waste in Mekong Delta, Vietnam. Biodiversitas 25: 4284-4291. Microorganisms play crucial roles in the decomposition of plant biomass. This study aimed to isolate, screen, and identify potential mesophilic cellulose-degrading bacterial (CDB) strains from natural compost from durian shells (DS). Results revealed that a total of fifteen aerobic strains were isolated at 37°C, thirteen of which exhibited enzymatic degradation of cellulose, with cellulolytic index (CI) values ranging from 0.34 to 3.22. Five strains with CI values greater than 2.0 presented potential extracellular cellulase enzyme activity, with carboxymethyl cellulase (CMCase) at 0.18-0.31 U/mL and filter paper cellulase (FPase) at 0.03-0.19 U/mL. The DSC.03 and DSC.04 strains showed the highest CMCase and FPase activities, respectively. Subsequently, molecular identification and phylogenetic analysis confirmed DSC.03 (PP851408.1) and DSC.04 (PP851410.1) isolates as Bacillus subtilis and Bacillus velezensis, respectively. The maximum bio-degradation percentages were 86.85% for filter paper and 48.72% for dry DS powder, which occurred in the mixed-culture treatment of the two selected strains after 15 days of incubation under shaking conditions at 150 rpm and 37°C. These findings indicate for the first time that natural durian shell compost contains potential cellulose-degrading bacterial communities with high extracellular enzyme-producing ability and active interactions with each other, which can be beneficial for the fermentation or composting of DS waste.